Aspectos físico-químicos e microbiológicos do rio Uberabinha: um diagnóstico da qualidade da água no município de Uberlândia (MG) - Harter, Luiz Vitor Leonardi (2007)
This research aimed to verify the quality of the Uberabinha River water (in Uberlândia - MG) through physic-chemical and microbiological analysis from samples taken during the rainy and the dry seasons. We established six points of sampling in areas with different characteristics: prior to the urban area, within the urban area and further on the urban area, which represents the rural area of Uberlândia. The samples were taken from October 2005 through October 2006. In each point there were five samples referring to: conductivity, biochemical oxygen demand (BOD), chemical oxygen demand (COD), detergents, oil and grease, dissolved oxygen (DO) hydrogen potential (pH), insoluble solid particles, water temperature, local temperature, fecal and total coliforms. The river throughput was determined in two spots along its way. The results have shown that the pollution rate is highly above the ones established by the legislation of CONAMA (National Council of Environment), showing that there is a great influence of the city of Uberlândia in the quality of the water from the Uberabinha River. The highest concentration of BOD and COD found was 37.0 mg/L O2 and 58.3 mg/L O2, respectively, all registered in November/2005. The lowest values of DO varied from 1.0 to 3.0 mg/L, all registered during the same period (November/2005). The proportion COD/BOD, for all the characteristics evaluated, was around 1.5, which means a polluting biodegradable mass. The main problems observed along the area studied are: deforesting, disorganized use and occupation of land (soil), soil pollution caused by solid residual dumping, that are taken into the river, and pollution generated by illegal sewage deposit, without previous adequate treatment.